Biodiversity of insect in Pequizeiro (Caryocar brasiliense, Camb.) at cerrado of Goiás State, Brazil - Ferreira, G. A.; Veloso, V. da Rocha Santos; Naves, R. Veloso; do Nascimento, J. L.; Chaves, L. J. (Agrociencia Uruguay, 2009)
The pequizeiro is considered a typical plant of Cerrado of the Brazilian Middle West, predominating on others in the environment, with elevated importance for the economy from Goiás. The objective of this research was to study the entomofauna occurrence, in pequizeiro plants of sixteen populations of Goiás State. There were evaluated 313 pequizeiro plants, through inspection of third part of the base of the plants. The insects were captured from parts of the plants, using entomologic net or through the laboratory. The behavior of the insects visitors was registered through observations, description and creation in laboratory of some species with high population to field. Also, data were logged according to the occurrence, place of attack or oviposition and type of symptoms. The Open pasture of the state of Goiás possesses rich entomofauna associated to the pequizeiro. The captured species and their respective occurrence percentage belong to the following orders: Hemiptera (25.64 %), Coleoptera (17.95 %), Lepidoptera (16.67 %), Hymenoptera (15.39 %), Diptera (11.54 %), Orthoptera (6.41 %), Neuroptera (2.56 %), Isoptera (1.28 %), Thysanoptera (1.28 %), Psicoptera (1.28 %). The species with the highest frequency in all the populations of pequizeiro were: Eulechriops sp. (100 %), Atta laevigatta (100 %), Eunica bechina (93.75 %), Lyriomisia sp. (93.75 %), Edessa rufomarginata (100 %), Rhodoneura intermedia (100 %) and Phydotricha sp. (81.25 %). The species Thagona tibiali, A. laevigatta, R. intermedia, Carmenta sp. e E. rufomarginata can be considered potential plague of pequizeiro at Cerrados of Goias State. Further studies are necessary to understand the population dynamic of these insects and their relations with the host from different eco-regions of Goiás cerrados.